ANALISIS PROSEDUR PENILAIAN ON THE SPOT (OTS) TENTANG KELAYAKAN PENYALURAN DANA PADA KPR SEJAHTERA BTN IB SYARIAH KANTOR CABANG PADANG (MENURUT PASAL 23 UU NO. 21 TAHUN 2008 TENTANG PERBANKAN SYARIAH) - Ghenda Yulandari; Sofia Ridha (Jurnal Ekonomi dan Bisnis, 2023)
KPR Sejahtera BTN iB Syariah is a financing product with sharia principles that is specifically subsidized by the government in collaboration with the Ministry of PUPR for low-income communities (MBR). The background of this research is the discrepancy in the application of the OTS assessment. The purpose of this study was to find out how the implementation of the OTS assessment regarding the Feasibility of Distribution of Funds to the KPR Sejahtera BTN iB Syariah Padang Branch Office (According to Article 23 of Law No. 21 of 2008 concerning Sharia Banking) and what obstacles were encountered when carrying out the OTS assessment on KPR Sejahtera BTN iB Syariah.This research is a field research by means of observation, interview and documentation. Namely, researching directly to the object of research to make observations and collect data to be analyzed. In this study the authors used a qualitative descriptive method. The main source of this research is the Bank, especially the Financing Administration Officer. The results of the study are that the implementation of the OTS assessment on KPR Sejahtera BTN iB Syariah Padang Branch Office has not been carried out in accordance with the provisions in Law no 21 of 2008 concerning sharia banking according to article 23 concerning the Eligibility of Distribution of Funds. As explained in article 23 paragraph (2) that Sharia Banks and/or UUS are required to carry out a careful assessment of the character, capabilities, capital, collateral and business prospects of prospective customers receiving fasilities. However, in the application of the five principles described in the law, it turns out that there are three prnciples that have not been fully implemented by the survey department to carry out a careful assessment, including the principles of character, capital and business prospects.